Uso de colorantes alimentarios (artificiales y naturales) y su impacto en la salud: revisión de la literatura. - Hidalgo Olmedo, Byron Geovanny (2022)
Nowadays, food consumption by the population is mainly based on the impression caused by their color, which helps to highlight the product, promoting a perception of freshness and quality. However, colorants are not of recent application since, according to literature, they date back to 3000 BC. However, colorants are not a recent application, since according to the literature they date back to 3000 B.C., which proves that colorants already existed at that time, and nowadays their application is massive in several products whose purpose is to mark their quality and increase the visual attraction of the consumer, even knowing that the excessive consumption of mostly synthetic colorants can cause damage to health, causing the development of allergies, difficulties in the nervous system and neurotransmission, among others, unlike several colorants of natural origin that due to their condition can have certain health benefits. The purpose of the study is to carry out a bibliographic review of the uses of artificial and natural colorants, determining their historical beginnings, advantages, disadvantages, specific characteristics and their impact on health. The applied methodology is of documentary type, by means of the bibliographic review of the literature, a bibliographic corpus obtained from the scientific databases SCOPUS and Web of Science (WoS) is created, in first instance 224 documents are collected and by means of the inclusion and exclusion criteria, 47 documents were finally selected for the development of the study. The results obtained indicate that artificial colorants cause several negative effects on health, however, their use is massive because they represent industrial advantages since they have better functional and technological characteristics and low cost, compared to those of natural origin, which could even provide important health benefits due to their anticarcinogenic and cardiovascular prevention properties. However, it is important to state that the use of the colorant will depend on the type of food to be processed and the current legislation on the use of additives in food. Therefore, it is necessary to raise awareness about the consumption of products with colorants, due to the health problems they cause with great influence on artificial food colorings, thus being able to educate the population about the products they ingest and their consequences on health.